National Transmission System Operators in an International Electricity Market - Henrik Horn; Thomas P. Tangerås (Research Institute of Industrial Economics (IFN), 2021)
This paper develops a framework for analyzing the incentives of national transmission system operators (TSOs) to supply cross-border interconnection capacity in an international electricity market. Our results show that equilibrium transmission capacity is downward distorted, even in situations where full capacity utilization is inefficient. We derive a method for quantifying these distortions and propose a market design that uniquely implements efficient dispatch of electricity. In this design, the distribution of trade adjustment payments causes TSOs to internalize the full effect of network congestion. The design would improve, for instance, on the current European market design.
Keywords: F12; F15; L43; L94; Q27; Q41; 330; International electricity market; Market design; Market power; Network congestion